Firm growth, survival and productivity in South Africa - Masenyetse, Rethabile Francis (School of Economics, 2018)
In developing economies, the existence of a healthy industrial structure is vital to the pursuit of long term policy objectives of employment and sustainable economic growth. This makes it important to understand the dynamics of firm survival and growth. There has been little attention on the topic in developing countries because of data limitations, which prevalent in most developing countries except for few countries with established stock exchanges such as South Africa. This thesis studies the relationship between firm growth, survival and productivity using South Africa as the case study and fills the gap in industrial organisation literature by providing new empirical evidence on developing countries. The first paper analyses the changing size distribution, concentration rates and reasons for non-survival. The data on companies listed in the Johannesburg Stock Exchange (JSE) during the period 2000-2010 is used. Firm sales is adopted as the main measure of firm size while assets are used for comparison purposes. Following the Law of Proportionate Effects (LPE) framework, it evaluates of the relative growth rates of large and small companies in general and at sectoral and industrial levels. The result indicates that smaller firms are growing faster than larger ones, and more interestingly it is the smallest of the small and medium firms that are growing the fastest indicating that the industrial structure in South Africa is quite healthy. This finding is robust to correction of potential econometric problems of sample selection bias, growth persistence and heteroscedasticity. The second paper considers the patterns of growth and survival and specifies a simple logit binary survival model that allows for firm and industry specific characteristics as determinants of survival. The model is improved upon using the non-parametric Kaplan-Meier product limit method and estimating Cox proportional hazard model. The results indicate that large firms, high leverage and profitability operating in the primary sector have higher probability of survival in South Africa. This is robust after taking into account the global financial crisis of 2008-2009. The last paper tests the validity of the link between firm finance and total factor productivity. Using leverage and liquidity are the indicators of finance, the results from panel data estimation indicates that low leverage firms are more productive compared to the high leverage, while the low liquid firms are less productive compared to high liquid firms. The results were subjected to a number of robustness tests to address potential econometric issues that may invalidate the findings.